Junie B. Jones loves handsome Warren - Park, Barbara; Brunkus, Denise (New York : Random House, 1996)
Unable to compete with her friends' fancy clothes and running ability, irrepressible six-year-old Junie B. finds her own way to make the new boy at school like her.
"A first stepping stone book."
Keywords: Friendship; Kindergarten; Schools